Pengembangan Permainan Ular Tangga Kimia sebagai Media Pembelajaran pada Materi Struktur Atom Kelas X SMA/MA - Yolanda Vitri; Iswendi Iswendi (Universitas Negeri Padang, 2021)
ABSTRACTThis study aims to produce a variety of exercises in the form of the Chemical Snakes and Ladders Game to strengthen students concepts on the Atomic Structure material and determine the level of validity of the media function. This type of research is Educational Design Research with a Plomp model consisting of 3 stages, namely: (1) preliminary research, (2) prototyping phase and (3) assessment phase. This research is limited to the stages of prototyping and formative evaluation to the stage of one to one and expert review. The expert review assessment was carried out with a validity test by 3 chemistry teachers at SMAN 7 Padang and 2 chemistry lecturers from FMIPA UNP. The data was sourced from validity questionnaire which was then analyzed using the Aiken's V formula. The validation results obtained an average V value of 0.83 with a valid category.Keywords: Chemical Snakes and Ledders Game, Learning Media, Atomic Structure, Plomp, Aikens VABSTRAKPenelitian ini bertujuan untuk menghasilkan variasi latihan berupa permainan ular tangga Kimia untuk memantapkan konsep peserta didik pada materi Struktur Atom dan menentukan tingkat validitas fungsi media. Jenis penelitian ini adalah Educational Design Research dengan model Plomp yang terdiri dari 3 tahap yaitu: (1) penelitian pendahuluan, (2) pembentukan prototipe dan (3) penilaian. Penelitian ini dibatasi pada tahap pembentukan prototipe dan evaluasi formatif hingga tahap one to one dan expert review. Penilaian expert review dilakukan dengan uji validitas oleh 3 orang guru kimia SMAN 7 Padang dan 2 orang dosen kimia FMIPA UNP. Data bersumber dari angket validitas yang kemudian dianalisis dengan formula Aikens V. Hasil validasi didapatkan nilai rata-rata V 0,83 dengan kategori valid. Kata Kunci: Permainan Ular Tangga Kimia, Media Pembelajaran, Strktur Atom, Plomp, Aikens V.